Governance of labour relations in the platform economy. The cooperation between YouTubers Union and IG Metall - Patrick Witzak; Markus Hertwig (Industrial Relations Journal, 2024)
The article focuses on the factors that explain the emergence and accomplishments of the `FairTube' campaign, which was initiated in 2019 by the YouTubers Union and the German metalworkers' union IG Metall, and was later established as a formalised German association (“Verein”). While the initial focus of the campaign was on changing the monetisation rules, which YouTube had altered very abruptly in 2017, the initiative subsequently focused on improving the working conditions of content creators. Methodologically, we deploy a mixed-methods design that flanks media discourse network analysis through qualitative content analysis of expert interviews, which helps to identify the interaction between these established and new actors in the governance and interest representation in the digital platform economy. Our findings reveal a `hybrid form of governance' that, by aligning ideologies and combining sources of power, was able to accomplish most of the goals set out by the campaign (avoiding arbitrary platform decisions, increasing transparency and communication, securing creators' income). We conclude that new forms of collective action, i.e. the coalition between “old” and “new” organizations, may mitigate particular negative consequences of the platform economy. The study seeks to contribute to a better understanding of platform work and to the concepts of power, ideas, and interests in industrial relations.
Keywords: 330